Comment on "Mistakes and inconsistencies regarding adsorption of contaminants from aqueous solution: A critical review, published by Tran et al. [Water Research 120, 2017, 88–116]". (1st February 2018) - Kopinke, Frank-Dieter; Georgi, Anett; Goss, Kai-Uwe
Abstract: Correct treatment of adsorption thermodynamics requires consistent handling of adsorption isotherms and the corresponding sorption coefficients. The present comment points to some inconsistencies and misunderstandings in a recent review article.